Additive-free Electrodeposition of SnCoNi Trimetallic Catalysts for Ethanol Electrooxidation - Salsabila, Qori'atun Ni'mah; Fabian Glorious Kenaya; Muhammad Fathar Aulia; Muhammad Athariq (Chemistry and Materials, 2024)
SnCoNi catalysts were synthesized via electrodeposition, with and without citric acid, to assess their ethanol electrooxidation performance. The additive-free catalyst exhibited superior properties, including lower charge transfer resistance and a smaller Tafel slope compared to the citric acid-modified catalyst. Chronoamperometry testing further revealed better electrochemical stability for the additive-free catalyst, with less current loss over time. Cyclic voltammetry confirmed the enhanced ethanol oxidation activity with a relatively high current density. The improved performance is attributed to better mass transport, active site exposure, and the synergistic effects of Sn, Co, and Ni in the additive-free catalyst, making it more efficient for ethanol electrooxidation. These findings suggest that the additive-free catalyst exhibits more favorable properties for ethanol electrooxidation compared to its citric acid-modified counterpart.